HUBUNGAN WAKTU RETURN TO SPORT DAN KEKUATAN OTOT DENGAN FUNGSI LUTUT DAN DAYA TAHAN OTOT PASCA ANTERIOR CRUCIATE LIGAMENT RECONSTRUCTION: Pendahuluan, Metode Penelitian, Hasil, Pembahasan, Simpulan, dan Daftar Pustaka - I Dewa Ayu Agung Friska Putri Indraswari; Kurniawati, Ida; I Putu Yudi Pramana Putra (Kinetic and Physiotherapy Comprehensive, 2023)
Background: Anterior cruciate ligament reconstruction (ACLR) is a surgical procedure performed to replace the ligament by grafting tissue that aims to restore stability to the knee joint. Knee function is impaired because the ligament that maintains knee stability is torn. Good knee function is also a reason to return to sports. Decreased muscle strength and endurance can occur in ACL patients, especially those who have undergone ACLR surgery. In order to be able to return to sport is still determined based on time after surgery and improved knee function. This study aimed to determine the relationship of return to sport time and muscle strength with knee function and muscular endurance after ACLR. Methods: The research method used a literature review compiled using secondary data from relevant journals. The search for journal literature was carried out online through PubMed and Google Scholar using the keywords "ACL", "return to sport", "function", "strength", and "endurance". Results: Based on the results of the journal review, it was found that muscle strength and endurance will decrease, which will affect knee function. Knee function, in general, is still one of the factors determining return to sport time. Conclusion: This study concluded that there were possible problems that arise due to ACLR, such as decreased muscle strength and muscle endurance, which could affect knee function and return to sports time.